SOCIAL POLICY IN THE PUBLIC ADMINISTRATION SYSTEM: ENSURING EQUAL ACCESS TO SOCIAL SERVICES - Banchuk-Petrosova, Olena; Solonenko, Oleksandr; Kobets, Yuliia (Public Management and Policy, 2025)
This article focuses on the analysis of the interaction between political processes and ethnic groups, with a particular emphasis on the causes of and strategies for resolving interethnic conflicts. The study employs an interdisciplinary approach, combining elements of political science, sociology, and other analytical perspectives. Among the key factors considered in the work are uneven distribution of power and resources between ethnic groups; limited access to economic opportunities for certain ethnic groups; and differences in language, religion, and traditions, which can lead to misunderstandings and conflicts. The article also presents ways to resolve interethnic conflicts, which include political science dialogue through the creation of platforms for open and constructive dialogue between representatives of different ethnic groups, the process of implementing programs aimed at reducing economic inequality and creating jobs, and promoting intercultural dialogue and exchange, which promotes mutual understanding and tolerance. The goal is to identify the main problems and factors that affect the effectiveness of the interaction of political processes and ethnic groups. The study is aimed at finding ways to improve interethnic confrontation and policies at the regional and national levels. The study used such methods as comparative analysis, statistical review, and methodology for assessing the effectiveness of the adoption of relevant programs. Among the key conclusions, it is worth noting: interethnic conflicts are a complex phenomenon that has deep historical, political, economic, and cultural roots; resolving interethnic conflicts requires a multilateral and comprehensive approach and includes the participation of all stakeholders; an important point is to counteract the spread of disinformation and incitement of interethnic hatred through the media.